Targeting Bacterial Communication: Evaluating Phytochemicals as LuxS Inhibitors to Disrupt Quorum Sensing - Yiannis Sarigiannis; Christos Papaneophytou (Macromol)
Bacterial quorum sensing (QS) is a critical communication process that regulates gene expression in response to population density, influencing activities such as biofilm formation, virulence, and antibiotic resistance. This study investigates the inhibitory effects of five phytochemicals—apigenin, carnosol, chlorogenic acid, quercetin, and rosmarinic acid—on the S-ribosylhomocysteinase (LuxS) enzyme, a key player in AI-2 signaling across both Gram-positive and Gram-negative bacteria. Using molecular docking studies, we identified that these phytochemicals interact with the LuxS enzyme, with apigenin, carnosol, chlorogenic acid, and rosmarinic acid binding within the substrate-binding pocket and exhibiting binding scores below −7.0 kcal/mol. Subsequent in vitro assays demonstrated that these compounds inhibited AI-2 signaling and biofilm formation in Escherichia coli MG1655 in a concentration-dependent manner. Notably, carnosol and chlorogenic acid showed the most potent effects, with IC50 values of approximately 60 μM. These findings suggest that these phytochemicals may serve as potential QS inhibitors, providing a foundation for developing new anti-pathogenic agents to combat bacterial infections without promoting antibiotic resistance. Further studies are warranted to explore the therapeutic applications of these compounds in both clinical and agricultural settings.